Pengaruh Locus of control Terhadap Komitmen Organisasi dan Kinerja Auditor (Studi pada inspektorat Daerah Provinsi Sulawesi Teggara) - Intani, Fitria; Haliah, Haliah (LP3M Universitas Kadiri, 2022)
In an effort to realize the vision and mission, strategic goals and objectives of the Regional Inspectorate of Southeast Sulawesi Province, the auditor's commitment to the organization is a form of attitude that also influences the achievement of the organization's vision and mission. This study aims to examine and analyze the effect of locus of control on organizational commitment and auditor performance at the Regional Inspectorate of Southeast Sulawesi Province. The results of this study indicate that: 1) Locus of control has a significant positive effect on organizational commitment. (2) Locus of control has a positive and significant effect on audit performance. (3) Organizational commitment has a positive and significant effect on auditor performance. (4) Locus of control has a positive and significant effect on auditor performance through organizational commitment. The conclusion of this study is that locus of control has a role or strength both externally and internally in determining employee attitudes and behavior towards the achievement of the vision and mission, goals and strategies of the organization.